Turnoverintention Reviewed of Workload with Job Satisfaction as Intervening Variable - Milda Mildawani; Nuraziza Listyaningrum (Perbanas Institute, 2023)
This study aims to determine the influence of workload on turnover intention through job satisfaction. Turnover intention is the cessation of an individual from one member of the organization concerned. Job satisfaction is a pleasurable emotional state resulting from job appraisal or work experience. Workloads are tasks assigned to workers or employees to be completed at a certain time. The method used is descriptive quantitative analysis method using a Likert scale measuring instrument. The research respondents were 80 employees of PT X. The results of the validity test showed that the valid statements of each variable were 8 of 9 items of turnover intention variable, 6 of 9 items of job satisfaction variable, 9 of 9 items of workload variable, with r arithmetic greater than r table = 0.22. The reliability test of the three variables was declared valid because it was greater than the Chronbach Alpha value = 0.7. The conclusion of this study is that H1, H2, H3 are supported and H4 is not supported. Keywords : Turnover Intention, Job Satisfaction, and Workload